LIVING QUR’AN: A PHENOMENOLOGICAL STUDY - Ali Murtadho; Moh. Najiburrahman (DAAR EL-KAMIL: Multidisciplinary Journal, 2025)
This research examines the phenomenon of the authority of the Qur’anic text in its interaction with local contexts through the Living Qur’an approach. Theologically, the Qur’an holds absolute authority as revelation; however, in social reality, this authority undergoes a process of recontextualization and negotiation to remain relevant to community culture. This study aims to describe how local communities receive and interpret the Qur’an beyond textual-normative boundaries. Using a qualitative method with a phenomenological approach, this research focuses on the subjective experiences of practitioners in religious activities. The theoretical framework includes Fazlur Rahman's thoughts on the Living Sunnah, Neal Robinson on audio-oral phenomena, and Ahmad Rafiq's classification of reception. The results indicate that in local contexts, the authority of the Qur’anic text transforms from cognitive authority to performative authority. Community reception is not merely exegetical but is predominantly aesthetic and functional, where the Qur’an is positioned as an "agency" that provides protection and spiritual identity. The conclusion of this study emphasizes that the Living Qur’an is a manifestation of the dynamization of revelation, keeping it alive (salih li kulli zaman wa makan) through creative dialogue with local wisdom without diminishing the sacredness of the original text.